2005
DOI: 10.1002/ijc.21599
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular profiling of platinum resistant ovarian cancer

Abstract: The aim of this study is to discover a gene set that can predict resistance to platinum-based chemotherapy in ovarian cancer. The study was performed on 96 primary ovarian adenocarcinoma specimens from 2 hospitals all treated with platinum-based chemotherapy. In our search for genes, 24 specimens of the discovery set (5 nonresponders and 19 responders) were profiled in duplicate with 18K cDNA microarrays. Confirmation was done using quantitative RT-PCR on 72 independent specimens (9 nonresponders and 63 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
127
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 49 publications
10
127
0
1
Order By: Relevance
“…In our study, we found a key DNA replication/ repair factor, proliferating cell nuclear antigen (PCNA) to be overexpressed in the cisplatin-resistant cell lines. Over the years, PCNA has been known to be involved in a broad base of metabolic pathways including DNA repair, and its overexpression is often found in drug-resistant cancer cell lines [37][38][39][40]. Overexpression of this protein in a resistant cell line suggests enhanced DNA repair activity which would inhibit cisplatin from causing cell death through cisplatin-DNA adduct formations.…”
Section: Dna Repair Proteinmentioning
confidence: 99%
“…In our study, we found a key DNA replication/ repair factor, proliferating cell nuclear antigen (PCNA) to be overexpressed in the cisplatin-resistant cell lines. Over the years, PCNA has been known to be involved in a broad base of metabolic pathways including DNA repair, and its overexpression is often found in drug-resistant cancer cell lines [37][38][39][40]. Overexpression of this protein in a resistant cell line suggests enhanced DNA repair activity which would inhibit cisplatin from causing cell death through cisplatin-DNA adduct formations.…”
Section: Dna Repair Proteinmentioning
confidence: 99%
“…Until now, very few markers were found to predict tumor response to chemotherapy and prognosis in ovarian cancer. [5][6][7] Recent advances in microarray technology led to identification of gene signatures that can help to improve diagnosis of ovarian cancer 8 and in vitro drug resistance 9,10 but not clinical response to chemotherapy. 11 We recently analyzed the gene expression patterns in advanced (FIGO stages III and IV) primary serous papillary carcinomas of the ovary displaying different response to first line chemotherapy in an attempt to identify specific molecular signatures associated with clinical response to chemotherapy.…”
mentioning
confidence: 99%
“…Combining both profiles yielded better prognostic discrimination than either profile alone. Helleman et al [13] identified a nine-gene profile using microarray and reverse transcription-polymerase chain reaction (RT-PCR) that was able to classify tumors from 24 patients according to their response to platinum-based therapy. Using RT-PCR, this nine-gene set predicted platinum resistance in an independent validation set of 72 patients.…”
Section: Microarray Studies In Ovarian Cancermentioning
confidence: 99%